Delik Pers dalam Perspektif Undang-Undang Perlindungan Konsumen - Samsul Wahidin (Jurnal Hukum IUS QUIA IUSTUM, 2001)
Although consumers Protection Act regulated on protection upon consuption goods, not all of them are protected. And even though press products can be qualified as consumption goods (such as information), the legal protection is based on the provisions of Press Act. With regard to press consumption, Consumers Protection Actis not Applicable